Case Report: Extensive Sublingual Epidermoid Cyst - Mochizuki Junior, Ciro [UNESP]; Camargo, Héric de Souza [UNESP]; Navarro, Claudia Maria [UNESP]; Bufalino, Andreia [UNESP]; Massucato, Elaine Maria Sgavioli [UNESP]; Monnazzi, Marcelo Silva [UNESP] (Springer Nature, 2025)
Introduction: Dermoid and epidermoid cysts are rare benign lesions in the oral cavity, commonly affecting the floor of the mouth. Though typically slow-growing, large cysts can impair speech, mastication, and swallowing, necessitating surgical intervention. Case Report: A 75-year-old man presented with a 9-cm sublingual lesion, progressively growing over 10 years and causing functional discomfort. Imaging revealed a well-defined cyst. Surgical excision via an intraoral approach was successful. Histopathology confirmed an epidermoid cyst. Conclusion: Surgical removal of large sublingual cysts can significantly restore oral function and quality of life. Accurate diagnosis and individualized treatment are essential for optimal outcomes.
Keywords: Functional rehabilitation; Oral cavity surgery; Sublingual epidermoid cyst